MAKNA KETUNTASAN DALAM BELAJAR - Hernawan, Asep Herry (MAJALAH ILMIAH PEMBELAJARAN, 2008)
The masteri learning issues are significant for students to achieve theirlearning outcomes, especially for students who have learningdifficulties. The emergence of mastery learning as one form ofeducational innovation has a main purpose to improve the motivationand studentsâ€™ effort to achieve the mastery level sufficiently. By usingthe mastery leaning approach to support the implementaion ofâ€œkurikulum tingkat satuan pendidikanâ€ (KTSP), everyone who isinvolved in the curriculum implementation has a responsibility tounderstand the mastery learning approach properly including itsdevelopment history, concept and the characteristics.